Creation and sharing of value in the telecoms sector. (How telecom operators' investments benefit content providers rather than themselves.) - François Jeanjean (International Telecommunications Society (ITS), 2024)
The fast technical progress coupled with a fierce competition in telecommunication markets urge operators to invest year after year a huge amount of investment. However, the maturation and saturation of markets prevents them from reaping the benefits. While telecommunication infrastructure improves fastly, the revenues of telecommunication operators tend to stagnate. Content providers are taking advantage of increased network capacity to offer more content that they are able to monetize. It is therefore they who benefit from the increase in network capacities and not the operators who nevertheless financed it. This article develops a theoretical model which highlights this mechanism and corresponds perfectly to empirical observations.
Keywords: D25; L51; L86; L96; 330; Competition; Investment; Telecommunication Operators; Content Providers